(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze the results of cesarean hysterectomy during and after delivery at Hanoi Obstetrics and Gynecology Hospital from January 2019 to December 2023. Materials and method: A retrospective descriptive cross-sectional study of 276 cases of cesarean hysterectomy during and after delivery at Hanoi Obstetrics and Gynecology Hospital from 2019 to 2023. Results: The primary method of cesarean hysterectomy was subtotal hysterectomy (97.1%), with the preservation of both adnexa in 98.9% of cases. The average blood loss was 1803 ± 120 ml. A total of 222 cases required blood transfusions, with an average of 2216 ± 2285 ml of blood transfused. The average duration of surgery was 88.1 ± 52.1 minutes. The average length of hospital stay after the hysterectomy was 6.2 ± 2.4 days. Conclusion: Cesarean hysterectomy during and after delivery is a major surgery with high risks. Obstetric surgeons must always be prepared for a hysterectomy and make early decisions to minimize blood loss and prevent complications.